HAK-HAK NARAPIDANA ANAK DI LEMBAGA PEMBINAAN KHUSUS RIGHTS OF CHILDREN IN SPECIAL CORRUPTION INSTITUTIONS - I Nyoman Gede Sugiartha (Faculty of Law, Mahasaraswati University, Denpasar, 2022)
Crimes against children are currently increasing in Indonesia, childrenare one of God's creations and at the same time are the children of the family. AsGod's creation, children under 18 years old or unmarried are still unstable intheir behavior, their unstable emotions should get full attention in correctionalinstitutions. This study aims to analyze the regulation of the child educationsystem in special coaching institutions and legal protection for child prisoners inspecial coaching institutions. This type of research uses an empirical method,using a Legislative and Conceptual approach. The problems raised; 1. Children'sRights in Prisoners Educated in Special Guidance Institutions. 2. Regulation ofchildren's rights in the criminal justice system in Indonesia. 3. ObstaclesExperienced by Officers in Fostering Child Prisoners in Special GuidanceInstitutions. Discussions and discussions include; Children's rights in the justiceand education system are regulated in the Law of the Republic of IndonesiaNumber 11 of 2012 concerning the Child Criminal Justice System while the legalprotection of children is regulated in the Law of the Republic of IndonesiaNumber 35 of 2014 amendments to Law Number 23 of 2002 About ChildProtection. Correctional officers must understand better and must be adapted tothe conditions and situation of Indonesia without ignoring the methods or rightsthat should be obtained by children who are in conflict with the law by othercountries that should be considered and imitated.